MAKING BODIES KOSHER The Politics of Reproduction among Haredi Jews in England - Kasstan, Ben (Fertility, Reproduction and Sexuality, 2019)
For Haredi Jews, reproduction is entangled with issues of health, bodily governance and identity. This is an analysis of the ways in which Haredi Jews negotiate healthcare services using theoretical perspectives in political philosophy. It is the first archival and ethnographic study of Haredi Jews in the UK and sits at the intersection of medical anthropology, social history and Jewish studies. It will allow readers to understand how reproductive care issues affect this growing minority population.